Food and nutrient intake among Sri Lankan adults - Joyce, Caroline A.; Gelli, Aulo; Caswell, Bess; Perera, Thushanthi; Ranathunga, Thilanka; Sitisekara, Hasara; Tan, Xiuping; Hess, Sonja Y.; Silva, Renuka; Olney, Deanna K.; Honeycutt, Sydney (International Food Policy Research Institute, 2023)
Healthy, balanced diets are crucial for preventing chronic diseases and disabilities, with fruit and vegetables (F&V) of particular importance. The CGIAR Research Initiative on Fruit and Vegetables for Sustainable Healthy Diets (FRESH) aims to enhance F&V intake, diet quality, nutrition and health while improving livelihoods, empowering women and youth and mitigating negative environmental impacts globally.